Brd4 Regulates the Homeostasis of CD8+ T-Lymphocytes and Their Proliferation in Response to Antigen Stimulation - Peng, Zhilin; Zhang, Yiwen; Ma, Xiancai; Zhou, Mo; Wu, Shiyu; Song, Zheng; Yuan, Yaochang; Chen, Yingshi; Li, Yuzhuang; Wang, Guanwen; Huang, Feng; Qiao, Yidan; et al. (Frontiers in Immunology, 2021)
CD8+ T cells are major components of adaptive immunity and confer robust protective cellular immunity, which requires adequate T-cell numbers, targeted migration, and efficient T-cell proliferation. Altered CD8+ T-cell homeostasis and impaired proliferation result in dysfunctional immune response to infection or tumorigenesis. However, intrinsic factors controlling CD8+ T-cell homeostasis and immunity remain largely elusive. Here, we demonstrate the prominent role of Brd4 on CD8+ T cell homeostasis and immune response. By upregulating Myc and GLUT1 expression, Brd4 facilitates glucose uptake and energy production in mitochondria, subsequently supporting naïve CD8+ T-cell survival. Besides, Brd4 promotes the trafficking of naïve CD8+ T cells partially through maintaining the expression of homing receptors (CD62L and LFA-1). Furthermore, Brd4 is required for CD8+ T cell response to antigen stimulation, as Brd4 deficiency leads to a severe defect in clonal expansion by decreasing glycolysis. Importantly, as JQ1, the specific inhibitor of Brd4, severely dampens CD8+ T-cell immune response, its usage as an anti-tumor agent or latency-reversing agent for human immunodeficiency virus type I (HIV-1) should be more cautious. Collectively, our study identifies a previously-unexpected role of Brd4 in the metabolic regulation of CD8+ T cell-mediated immune surveillance and also provides a potential immunomodulation target.